Color lab for mixed-media artists ; 52 exercises for exploring color concepts through paint, collage, paper, and more - Forman, Deborah (Lab series., 2015)
"Create the very best mixed media with 52 inspiring exercises! Strenthening your understanding and use of color will make your mixed-media art shine as you complete 52 labs that span painting, collage, drawing, assemblage and more.In Color Lab for Mixed Media Artists, color is explored through multiple lenses-nature, history, psychology, expression-as you work through 52 exciting and approachable projects that explore the infinite potential of the chromatic experience.Artist and color-theory expert Deborah Forman provides you with techniques and instruction. These materials and labs focus primarily on paint and collage, along with experimental projects for book making, sculpture and installation. Work your way through the color spectrum, using the steady beat of color as the guiding framework.Don't be intimidated by color--understand how it works, what shade, tint, and pure color will work for your project, and how to select, mix, or pair colors. When you're done, you'll have 52 personal, meaningful, outstanding, and colorful projects and the inspiration to create many more!"-- Provided by publisher.